Reimagining state responsibility for workers following COVID-19: A vulnerability approach. Issue 3 (September 2021) - Rodgers, Lisa
In this article it is argued that the COVID-19 crisis offers an important opportunity for engagement and reflection on the operation and effectiveness of laws regarding the workplace in the UK and beyond. The crisis underscores the temporality and partiality of labour law measures, and the need for a reimagining of that law based on more sustainable principles. I argue that this reimagination should coalesce around a human-centric approach to law, and the recognition of the need for deep and varied institutional support for workers. It is argued that these principles have been adopted historically in the context of health and safety law, but have not always been well applied, particularly in the context of the pandemic. In any event, the adoption of these principles and the greater integration of health and safety and labour law would encourage states to better promote worker agency and resilience and hence move towards meeting the aspirations of vulnerability theory.